2012
DOI: 10.1038/jid.2012.14
|View full text |Cite
|
Sign up to set email alerts
|

Doxycycline Indirectly Inhibits Proteolytic Activation of Tryptic Kallikrein-Related Peptidases and Activation of Cathelicidin

Abstract: The increased abundance and activity of cathelicidin and kallikrein 5 (KLK5), a predominant trypsin-like serine protease (TLSP) in the stratum corneum, have been implicated in the pathogenesis of rosacea, a disorder treated by the use of low-dose doxycycline. Here we hypothesized that doxycycline can inhibit activation of tryptic KLKs through an indirect mechanism by inhibition of matrix metalloproteinases (MMPs) in keratinocytes. The capacity of doxycycline to directly inhibit enzyme activity was measured in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
81
1
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(92 citation statements)
references
References 49 publications
(53 reference statements)
0
81
1
7
Order By: Relevance
“…Traditional US Food and Drug Administration (FDA)-approved topical treatments include topical sodium sulfacetamide, azelaic acid, and metronidazole. The only FDAapproved systemic medication for rosacea is subantimicrobial-dose doxycycline [11,12]. Several new treatment options were recently FDA approved or are in clinical trials.…”
Section: Introductionmentioning
confidence: 99%
“…Traditional US Food and Drug Administration (FDA)-approved topical treatments include topical sodium sulfacetamide, azelaic acid, and metronidazole. The only FDAapproved systemic medication for rosacea is subantimicrobial-dose doxycycline [11,12]. Several new treatment options were recently FDA approved or are in clinical trials.…”
Section: Introductionmentioning
confidence: 99%
“…One potential mechanism of action for doxycycline in the treatment of rosacea is indirect inhibition of KLK proteolytic activities and cathelicidin peptide LL-37 production by inhibiting MMPs in keratinocytes. 37 Decreased KLK activity is reported when doxycycline or other MMP inhibitors are added to live keratinocytes during KLK production. 37 …”
Section: Oral Therapymentioning
confidence: 99%
“…37 Decreased KLK activity is reported when doxycycline or other MMP inhibitors are added to live keratinocytes during KLK production. 37 …”
Section: Oral Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…48 Through inhibition of numerous matrix metalloproteinases, a reduction in the quantity and activity of serine protease kallikrein 5 results in decreased production of cathelicidin LL-37, the same AMP that has been highlighted in the pathogenesis of rosacea. 49 Key anti-inflammatory actions of doxycycline in rosacea include: downregulation of cytokines, reducing neutrophil infiltration, inhibition of nitric oxide and its vasodilatory effects, reduction of reactive oxygen species, slowing connective tissue destruction, and inhibition of matrix metalloproteinases. 50 Several studies have shown the effectiveness of doxycycline at subantimicrobial doses in the treatment of PPR, both as monotherapy and in conjunction with topical agents.…”
Section: Systemic Therapiesmentioning
confidence: 99%